Vitamin D deficiency and its role in the development of cardiovascular diseases - I. G. Kinvanlun; N. E. Zemlyanaya (Clinical Medicine (Russian Journal), 2026)
Cardiovascular diseases (CVD) are the leading cause of death in the world. This review analyzes the role of vitamin D deficiency as a risk factor for CVD, including hypertension, coronary heart disease, heart failure, and stroke. Vitamin D defi ciency (25(OH) D < 30 ng/ml) occurs in 30–50% of the population, especially in regions with low insolation. Epidemiological data confi rm a 1.5–2-fold increase in the risk of CVD with low vitamin D levels. Pathophysiological mechanisms include endothelial dysfunction, infl ammation, dyslipidemia, and activation of the renin-angiotensin-aldosterone system. Clinical studies (VITAL, D-Health) show contradictory results: taking vitamin D is eff ective only in groups with severe deficiency. Further research is needed to develop personalized approaches to CVD prevention. Material and methods. A review of the scientific literature (2014–2025) was conducted based on a search in the PubMed, Scopus, and eLibrary databases. Data from meta-analyses, large cohort studies (Framingham, Rotterdam), and randomized controlled trials (VITAL, D-Health) were analyzed. The sources were selected based on the criteria of relevance, design quality, and evidence.